Prognostic factors for survival in pancreatic cancer patients from university Malaya medical centre, Malaysia - Malwinder, Singh; Wan Zamaniah, Wan Ishak; Cimmeran, Kaur; Phua, Vincent Chee Ee (University of Malaya Medical Centre, 2018)
Objectives: Pancreatic cancer is an aggressive silent killer with a median survival of a few months. It is the fourth leading cause of cancer death in the United States. The aim of this study was to evaluate the prognostic factors affecting the survival of patients with adenocarcinoma of the pancreas in Malaysia. Methods: This retrospective study examined 107 patients with adenocarcinoma of the pancreas from 2002 to 2012 at University Malaya Medical Centre. The factors evaluated were age, sex, race, smoking habits, performance status, the presence of jaundice, pre-treatment CA 19.9 serum level, the location of a primary tumour, tumour grade, tumour staging and intent of treatment. Results: The median survival for the overall study population was 7.0 months (95% CI 5.1-8.8 months) with 1, 3, and 5-year survival rates of 30.8%, 8.4% and 3.7% respectively. The survival was 16.1 months (95% CI 7.7-24.4 months) for stage 1, 15.5 months (95% CI 8.1-22.8 months) for stage 2, 8.4 months (95% CI 6.1-10.8 months) for stage 3, and 3.8 months (95% CI 2.9-4.7 months) for stage 4. In multivariate analysis, independent and unfavourable prognostic factors which retained significance were performance status, tumour stage and treatment intent. Conclusions: The biological characteristics are important as predictors of survival in patients with pancreatic cancer. Longer survival is possible if the disease is identified in its early stages with good performance status. Further development and evaluation of novel screening strategies need to be established to improve early detection of this disease.